Konsepsi Penerapan Keterampilan Proses Sains (KPS) dan Sikap Ilmiah Dalam Desain Pengembangan Modul Panduan Eksperimen Ipa SD/MI - fiteriani, ida; Baharuddin, Baharuddin (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2018)
This research moved from the problem of the lack of availability of science books (modules) based on the development of science process skills (scienific process) and scientific attitude of students. Generally textbooks that are often used by teachers or students emphasize mastery of science concepts (scientific knowledge), while science process skills (scienific process) and what scientific attitudes to be developed are not clearly defined and detailed, so that the impact on activity and acquisition of student learning outcomes. Based on the description of the above problems, the purpose of this research and development is to produce a product in the form of an experimental module for science in elementary school that based on science process skills (scienific process) and scientific attitudes, expecially in term : Human Circulatory System. The model used refers to Borg and Gall. To assess the feasibility of the module, validation was carried out by experts (material experts, media experts, and linguists) and also involved education practitioners. To assess the attractiveness of the module a trial was conducted, which began with a small group and then in a large group. Furthermore, the process of data analysis uses quantitative and qualitative techniques. The research and development (R D) results are 1) The development step begins with analyzing potential and problems, collecting data / information, designing products, validating products, revising products, conducting product feasibility trials, and revising products again. 2) Based on the results of validation and feasibility tests, the development of the science module experiment for SD / MI based on science process skills (scienific process) and scientific attitudes in the term of the Human Circulatory System successfully meet the level of feasibility and attractiveness, therefore it can be used as teaching material in science learning in elementary school (SD/MI)